Design, Implementation and Evaluation of IPv4/IPv6 Longest Prefix Match support in P4 Dataplanes - Cesen, Fabricio E. Rodriguez; Patra, P. Gyanesh Kumar; Rothenberg, Christian Esteve; Pongracz, Gergely (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2018: Anais do XVII Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2018.3319, 2018)
New trends in dataplane programmability inside Software Defined Networking (SDN) paradigm are in an effort to bring multi-platform support with a high-level definition of the dataplane pipeline functions. The Multi-Architecture Compiler System for Abstract Dataplanes (MACSAD) can integrate the Protocol-Independent Packet Processors (P4) domain-specific language and the OpenDataPlane Project (ODP) APIs, to define a programmable dataplane across multiple targets in a unified compiler system. In this paper, we present and evaluate the IPv4/IPv6 Longest Prefix Match (LPM) support in MACSAD. We develop a new ODP Helper library implementing the IPv6 lookup mechanism based on the current IPv4 solution and evaluate its performance and scalability for diverse workloads and target platform configurations.